Record-keeping systems for beef safety and feedlot health - C.D. Cranwell; D.D. Simms (Kansas Agricultural Experiment Station Research Reports, 1992)
Three hundred nine feedlots were mailed questionnaires to ascertain the types of recordkeeping systems currently being used to monitor health programs and FDA-specified treatment withdrawal times. Microcomputer systems were of special interest. Approximately one third of the feedlots responded. A majority with a one-time feeding capacity of more than 10,000 head were using a microcomputer record-keeping system, whereas most of those with fewer than 10,000 head used a manual, paper-based system. Those feedlots using computerized record-keeping systems had purchased their software package from one of five companies. Managers felt these software packages were adequate for billing customers, monitoring pharmaceutical inventory and withdrawal period, and aiding treatment diagnosis. Proper monitoring of animal inventory was indicated by some feedlots as a limitation of their particular software. Almost all feedlots using computer record-keeping systems indicated that fewer than five employees operate the system on a regular basis. Among feedlots using computerized systems, the scope of the particular software in use met the yards' perceived needs. Approximately 23% of responding feedlots regularly used blood or urine tests to verify proper drug withdrawal and clearance prior to shipping previously treated cattle.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Drug withdrawal; Record keeping; Microcomputer